2022
DOI: 10.3389/fnagi.2022.933853
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Eye Diseases in Individuals With Mild Cognitive Impairment and Alzheimer's Disease

Abstract: IntroductionAlzheimer's disease (AD) and age-related eye diseases pose an increasing burden as the world's population ages. However, there is limited understanding on the association of AD/cognitive impairment, no dementia (CIND) with age-related eye diseases.MethodsIn this cross-sectional, memory clinic-based study of multiethnic Asians aged 50 and above, participants were diagnosed as AD (n = 216), cognitive impairment, no dementia (CIND) (n = 252), and no cognitive impairment (NCI) (n = 124) according to in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 45 publications
0
1
0
Order By: Relevance
“…While a substantial proportion of patients across diagnostic groups had ocular pathology, which is common in older age and populations of patients with dementia, 37 these factors did not affect the diagnostic ability of qLRP in sensitivity analyses. Earlier studies on qLRP have, with few exceptions, 38 excluded patients with even mild ocular disorders.…”
Section: Discussionmentioning
confidence: 84%
“…While a substantial proportion of patients across diagnostic groups had ocular pathology, which is common in older age and populations of patients with dementia, 37 these factors did not affect the diagnostic ability of qLRP in sensitivity analyses. Earlier studies on qLRP have, with few exceptions, 38 excluded patients with even mild ocular disorders.…”
Section: Discussionmentioning
confidence: 84%
“…Recent studies have found that the incidence of DR correlates with brain neurodegenerative diseases like AD, and both these are involved with neurodegeneration and abnormal vascular functioning during development ( Chua et al, 2022 ). A cohort study that included 134,327 diabetic patients above 60 years of age demonstrated that there was a higher percentage of patients with DR developing AD than diabetic patients without DR ( Pedersen et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%